Sustainability, risk, and business intelligence in supply chains - (:unkn) unknown (IGI Global, 2018)
Sustainable Supply Chain Management has become one of the most important managerial trends nowadays. Companies can optimize their supply chains by integrating risk management and sustainability programs. This chapter explains sustainability and risk management concepts in supply chains and discusses the relationship between these two issues in a multidirectional way. Business Intelligence tools are addressed in terms of their role and importance in supporting the management of supply chains, their risks and sustainability. The aim of the chapter is to provide a background to better understand the link between supply chain risk management, sustainability and business intelligence. © 2018, IGI Global.